Między Wallenrodem a Irydionem. Rzecz o Rozdzióbią nas kruki, wrony… Stefana Żeromskiego - Flis-Czerniak, Elżbieta (Poznańskie Studia Polonistyczne. Seria Literacka, 2016)
In the opinion of the author of this article, Żeromski, showing a tragic picture of the January Uprising in Ravens and Crows Will Peck Us to Pieces, runs very skillfully polemic with the views of Stanislaw Tarnowski, both political and social, which are summarized in the hearing From the experiences and reflections, as well as the aesthetic-literary ones, expressed among other things in the works devoted to Arthur Grottger, Polish romantics or in reviews of Sienkiewicz’s historical novels. Irydion and Konrad Wallenrod play a special role in the intricate network of intertextual references presenting in Żeromski’s story. Count Stanislaw Tarnowski spoke many times about these literary works, occupying a unique position in the minds of Poles living in the 19th century. His writings designate the area of controversy, which is the foundation of imaginative and ideological construction of Żeromski’s story Ravens and Crows Will Peck Us to Pieces.